Introducing the “SOAC Wrist”: Scaphotrapeziotrapezoid Osteoarthritis Advanced Collapse - Oliveira, Ricardo Kaempf de; Aita, Márcio; Brunelli, João; Carratalá, Vicente; Delgado, Pedro J (Revista Iberoamericana de Cirugía de la Mano, 2020)
Despite being the second most common osteoarthritis of the wrist, little is known about scaphotrapeziotrapezoid osteoarthritis. Not all patients with this type of osteoarthritis have symptoms, and, even in those symptomatic patients, the intensity of the complaint is not proportional to the severity of the degeneration. In symptomatic patients, when the conservative treatment fails, grading classifications to help define the surgical treatment are solely based on the joint characteristics, and fail to assess the rest of the carpus.In general, most carpal degenerative processes show the same evolution pattern, which varies according to the initial injury, along with the type of deformity and the inherent instabilities. Thus, we hypothesize that the degenerative evolution due to primary osteoarthritis of the scaphotrapeziotrapezoid joint also follows a logical evolutionary sequence, similar to the one that occurs in cases of scapholunate advanced collapse (SLAC), scaphoid nonunion advanced collapse (SNAC), scaphoid malunion advanced collapse (SMAC), and scaphoid chondrocalcinosis advanced collapse (SCAC), thus resulting in scaphotrapeziotrapezoid osteoarthritis advanced collapse (SOAC). We have divided the SOAC into three groups, and considered that their treatment shall be guided by the evolutionary stage of the disease, and not by the surgeon's preferred technique.A pesar de constituir la segunda causa más común de artrosis de la muñeca, poco se conoce sobre la artrosis escafotrapeciotrapezoidea. No todos los pacientes con este tipo de artrosis presentan síntomas, y, incluso en los pacientes sintomáticos, la intensidad de las quejas no es proporcional a la gravedad de la degeneración. En los pacientes sintomáticos, cuando fracasa el tratamiento conservador, las clasificaciones de los grados para ayudar a definir el tratamiento quirúrgico se basan únicamente en las características de la articulación, y no evalúan el resto del carpo.En general, la mayoría de los procesos degenerativos carpianos muestra el mismo patrón de evolución, el cual varía de acuerdo con la lesión inicial junto con el tipo de deformidad y las inestabilidades inherentes. Por lo tanto, nuestra hipótesis es la de que la evolución degenerativa debida a la artrosis primaria de la articulación escafotrapeciotrapezoidea también obedece a una secuencia evolutiva lógica, similar a la que ocurre en el colapso avanzado escafolunar scapholunate advanced collapse (SLAC), scaphoid nonunion advanced collapse (SNAC), scaphoid malunion advanced collapse (SMAC), and scaphoid chondrocalcinosis advanced collapse (SCAC), thus resulting in scaphotrapeziotrapezoid osteoarthritis advanced collapse (SOAC). Hemos dividido al SOAC en tres grupos, y consideramos que su tratamiento deberá estar guiado por la etapa evolutiva de la enfermedad, y no por la técnica preferida por el cirujano.
Keywords: Scaphotrapeziotrapezoid(STT) joint; arthritis; classification; arthroscopy/use